Individualization of Migraine Prevention: A Randomized Controlled Trial of Psychophysical-based Prediction of Duloxetine Efficacy. Issue 9 (September 2019) - Kisler, Lee B.; Weissman-Fogel, Irit; Coghill, Robert C.; Sprecher, Elliot; Yarnitsky, David; Granovsky, Yelena
Abstract : Objective: Finding an effective preventive agent for the individual migraineur is often long and frustrating. An individual-specific, efficacy-predicting tool would be invaluable in directing, shortening, and improving this process. As the serotonin-norepinephrine reuptake inhibitor duloxetine is a pain modulator, we hypothesized that pronociceptivity will directly predict drug efficacy, so that the more pronociceptive the patient is, the more efficacious the drug. Therefore, we used psychophysical pain measures to predict duloxetine efficacy in migraine prevention. Methods: Fifty-five migraineurs participated: 27 received duloxetine and 28 nonactive placebo. Responses to painful stimuli, conditioned pain modulation, and temporal summation of pain were measured before treatment. Treatment outcome measures included changes in attack frequency, migraine days, pain levels, and a reported self-estimate of migraine improvement at weeks 4 and 5. To examine treatment effects, the outcome measures were compared with pretreatment levels. Treatment by the psychophysical-predictor effect on treatment outcome was examined in separate regression models. Results: Duloxetine was more efficacious than placebo in migraine prevention, as indicated by the patient's estimation of migraine improvement (duloxetine: 52.3±30.4%; placebo: 26.0±27.3%; P =0.001). Further, this measure, in the duloxetine group, was predicted by higher pretreatment pain ratings for tonic heat pain ( P =0.012); greater pain sensitivity at baseline predicted greater percent of migraine improvement in duloxetine ( r =0.47; P =0.013), but not in placebo ( r =−0.36; P =0.060). Discussion: Our results suggest how personalized medicine can be applied to designing appropriate migraine prevention treatment. Psychophysical testing can reveal and characterize pronociceptive migraineurs, who seem to be more likely than non–pronociceptive ones to benefit from migraine prevention with serotonin-norepinephrine reuptake inhibitors. Abstract : Supplemental Digital Content is available in the text.